The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/chd.12120
|View full text |Cite
|
Sign up to set email alerts
|

Midgestation Fetal Pulmonary Annulus Size Is Predictive of Outcome in Tetralogy of Fallot

Abstract: Background Surgical management of tetralogy of Fallot (TOF) is increasingly moving towards valve-sparing approaches rather than transannular patch (TAP). We evaluate if fetal pulmonary valve (PV) size is predictive of postnatal course and surgical approach in TOF. Methods In this retrospective study, fetal and postnatal demographic, clinical and echocardiographic data on 66 patients diagnosed prenatally with TOF were collected. We compared those with mid-gestation PV z-score >-3.5 to those ≤ -3.5. We analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 24 publications
(57 reference statements)
6
10
0
Order By: Relevance
“…Previous studies have demonstrated that key prenatal echocardiographic features like pulmonary valve hypoplasia and reversal of ductal flow are predictive in determining degree of cyanosis . Our study validates that PV size associates with ESI later in pregnancy.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Previous studies have demonstrated that key prenatal echocardiographic features like pulmonary valve hypoplasia and reversal of ductal flow are predictive in determining degree of cyanosis . Our study validates that PV size associates with ESI later in pregnancy.…”
Section: Discussionsupporting
confidence: 86%
“…Given this, prior studies have demonstrated prenatal factors predictive for early intervention. These studies have shown that flow reversal in the arterial duct, small pulmonary valve size and failure of development of the pulmonary trunk has correlated with need for early intervention. Recent studies have evaluated cerebrovascular blood flow and flow dynamics in patients with congenital heart disease .…”
Section: Introductionmentioning
confidence: 99%
“…A pulmonary annulus Z ‐score of –4 or higher was reported to be a good marker for successful PVSS repair. Prenatally, a pulmonary valve Z ‐score ≤ –3.5 in the second trimester and increased pulmonary valve peak systolic velocity ≥ 87.5 cm/s were found to be useful in predicting need for TAP repair and earlier intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few previous studies have evaluated the association between fetal echocardiographic parameters and postnatal outcomes in TOF and the evaluated cohorts are often small [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%